Randomized, Double Blind, Placebo Controlled, Clinical Trial to Study Ashwagandha Administration in Participants Vaccinated Against COVID-19 on Safety, Immunogenicity, and Protection With COVID-19 Vaccine–A Study Protocol - Chopra, Arvind; Chavan-Gautam, Preeti; Tillu, Girish; Saluja, Manjit; Borse, Swapnil; Sarmukaddam, Sanjeev; Chaudhuri, Susmita; Rao, BCS; Yadav, Babita; Srikanth, Narayanam; Patwardhan, Bhushan (Frontiers in Medicine, 2022)
ABSTRACT Introduction: Vaccines have emerged as the most effective tool in the fight against COVID-19. Governments all over the world have rolled out the COVID-19 vaccine program for their populations. Oxford-AstraZeneca COVID-19 vaccine (COVISHIELD™) is widely used in India. A large number of Indian people have been consuming various traditional medicines in the hope of better protection against COVID-19 infection. Several studies have reported immunological benefits of Withania somnifera (Ashwagandha) and its potential as a vaccine adjuvant. We propose to study the safety, immunogenicity, and clinical protection offered by a six-month regimen of Ashwagandha in participants who volunteer to be vaccinated against COVID-19 (COVISHIELDTM) in the ongoing national program of vaccination. Methods and analysis: We designed a prospective, randomized, double-blind, parallel-group, placebo-controlled, two-arm, exploratory study on healthy volunteers receiving the COVISHIELDTM vaccine. The administration of Ashwagandha will begin within 7 days of the first or second dose of COVISHIELDTM. Primary outcome measure is immunogenicity as measured by SARS-CoV-2 spike (S1) and RBD-specific IgG antibody titres. Secondary outcome measures are safety, protective immune response and quality of life measures. All adverse events will be monitored at each time throughout the study. Participants will be tracked on a daily basis with a user-friendly mobile phone application. Following power calculation, 600 participants will be recruited per arm to demonstrate superiority by a margin of 7% with 80% power. Study duration is 28 weeks with interim analysis at the end of 12 weeks. Ethics and dissemination: Ethics approval was obtained through the Central and Institutional Ethics Committees. Participant recruitment is expected to commence by November 2021. Results will be presented in conferences and published in preprint followed by peer-reviewed medical journals. Registration details: Clinical Trial Registry – India (CTRI) Registration Number: CTRI/2021/06/034496. Date of Registration June 30, 2021.